the possible factors are (b-2) and (3a+4) but out of the possible following choice tho the answer would be (3a+4)
The expression 2a - 4 is a factor of 3ab - 6a + 4b - 8.
The expression 2a - 4 is a factor of 3ab - 6a + 4b - 8.
To check if an expression is a factor, we can substitute the values of a and b into the expression and see if it simplifies to zero. When we substitute a = 1 and b = 2 into 2a - 4, we get 2(1) - 4 = 2 - 4 = -2. And when we substitute these values into 3ab - 6a + 4b - 8, we get 3(1)(2) - 6(1) + 4(2) - 8 = 6 - 6 + 8 - 8 = 0. Since the expression evaluates to zero, it is a factor of the given expression.
#SPJ3
Answer:
-22
Step-by-step explanation:
18 + 4 = 22
then just add the negative to 22
-22
Answer:
-22
Step-by-step explanation:
-18 - 4 = 22
219.8 mm2
B.
341.6 mm2
C.
170.8 mm2
D.
390.6 mm2